2012
DOI: 10.1080/09585192.2011.560884
|View full text |Cite
|
Sign up to set email alerts
|

Career attitudes and success of managers: the impact of chance event, protean, and traditional careers

Abstract: Available online iFirstInternational audienceWe propose a career model that focuses on the antecedents of career success for managers and professionals within organizations. The model includes constructs rarely represented in the literature, and is based on conservation of resources theory. Testing our model with a sample of 545 managers, we found significant effect of positive and negative social capital, perception of organizational politics, professional vitality, and protean career attitude on internal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 79 publications
6
96
0
3
Order By: Relevance
“…Bright, Pryor, and Harpham (2005) argued that given their apparent ubiquity, dismissing chance events as merely error, will continue the tradition of providing accounts of career behavior so far removed from the actual career development experience of individuals and their counselors, that such accounts will remain fundamentally irrelevant to both. (p. 574) Our study lends support to chance events approaches to boundaryless careers, especially those approaches that juxtapose chance encounters, social networks, and protean orientations (e.g., Grimland et al, 2012). In her study of international acclaimed opera singers, Diaz De Cumanciero (2004) observed that while in science serendipity refers to the accidental discovery of the unsought for, in the performing arts it is the artist who is discovered by audiences and critics and acclaimed as a new star by the media:…”
Section: Alternative Explanationsmentioning
confidence: 84%
See 2 more Smart Citations
“…Bright, Pryor, and Harpham (2005) argued that given their apparent ubiquity, dismissing chance events as merely error, will continue the tradition of providing accounts of career behavior so far removed from the actual career development experience of individuals and their counselors, that such accounts will remain fundamentally irrelevant to both. (p. 574) Our study lends support to chance events approaches to boundaryless careers, especially those approaches that juxtapose chance encounters, social networks, and protean orientations (e.g., Grimland et al, 2012). In her study of international acclaimed opera singers, Diaz De Cumanciero (2004) observed that while in science serendipity refers to the accidental discovery of the unsought for, in the performing arts it is the artist who is discovered by audiences and critics and acclaimed as a new star by the media:…”
Section: Alternative Explanationsmentioning
confidence: 84%
“…You just don't know. (in Wattenberg, 2000) Pollack's comment about the risks the director takes in trying to bring novel elements into the filmmaking process also illustrates the self-directed and value-driven protean career orientation (Grimland, Vigoda-Gadot, & Baruch, 2012;Hall, 2004), which was dominant in all 12 directors. This is not surprising, considering that directorial careers cannot be psychologically owned or managed by any organization but by the directors themselves.…”
Section: Critical Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding challenges associated with appropriate terminology, definitions (Rice 2014) and appropriate methodologies (Cabral & Salomone 2009;and Chen 2005), the broad careers literature generally supports this study's findings regarding the influence of chance events and personal agency, and the changes that occur at the intersections between these two influences (Blanco & Golik 2015). There is also acknowledgement that chance events can have both positive and negative impacts on career trajectories (Grimland et al 2012), although participants in the current study associated chance events with primarily positive outcomes. Hancock (2009) emphasises that chance events that impact career trajectories are not necessarily related to the employment context, as was the case in this study, whereby participants spoke of the indirect influences of chance events associated with the timing of national economic policies, access to personal financial resources, family support, and personal relationship changes.…”
Section: Both Chance Events and Personal Agency Impact Ecps' Career Tmentioning
confidence: 98%
“…An individual's cultural background, for instance, may affect her/his perception of chance events (Grimland et al 2012). Colonial policies like imperialism, social policies that attempt to strengthen the welfare state, and discriminatory practices based on racism and ageism might also result in chance events that negatively impact certain individuals more than others (Grimland et al 2012).…”
Section: Both Chance Events and Personal Agency Impact Ecps' Career Tmentioning
confidence: 99%